(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The existence of street vendors around the Kelapa II Entrop considered to be the cause of traffic congestion and disturb the beauty of the City. Along with the increase in street vendors Departement of industry and commerce specifically the trade department do arrangement to street vendors by registering also socializing and prepare a place for traders. The purpose of this study to find out how the street vendor arrangement policy. The method used this study is a qualitative by using method of observation,interviews,and documentation. Result of the study shows that policy implementation of the street vendors arrangementat not maximal, this is due to several problem and obtacles that keep trader from selling. Keywords : implementation, policy, street vendors arrangement